Optimization of Direct Organogenesis and Callus Induction in Curcuma sumatrana Miq. for Conservation and Biotechnology (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Curcuma sumatrana Miq. is a rare ginger species endemic to Sumatra, Indonesia, and is listed as Vulnerable (VU) by the IUCN. The plant holds significant pharmacological potential, but severe habitat degradation and illegal harvesting threaten its existence before its full potential can be explored. This study aimed to develop an in vitro micropropagation protocol as a strategic approach for ex situ conservation and sustainable mass propagation. Explants from rhizome buds were cultured on Murashige & Skoog (MS) medium supplemented with various combinations of plant growth regulators (PGRs). The results showed that the combination of 5.0 mg/L 6-benzylaminopurine (BAP) and 0.5 mg/L 1-naphthalene acetic acid (NAA) yielded the highest shoot proliferation (an average of 2.33 shoots per explant) and the longest shoots (4.47 cm). For root induction, the medium with 0.5 mg/L BAP and 1.0 mg/L NAA provided the most optimal response (3.33 roots per explant). Indirect regeneration via callus induction was successfully achieved using 6.75 mg/L 2,4-dichlorophenoxy acetic acid (2,4-D) and 2.2 mg/L BAP, producing a compact callus. The use of Plant Preservative Mixture (PPM™) at 1.0 mL/L was also proven effective in controlling contamination without phytotoxic effects. The developed protocol provides a crucial foundation for the ex situ conservation and mass propagation of C. sumatrana. This success not only supports the protection of an endangered species but also opens up opportunities for the sustainable production of bioactive compounds, thereby reducing the pressure on its natural populations.
Keywords: In vitro culture; shoot proliferation; root induction; vulnerable species